PROBLEMS FACED BY WOMEN ENTREPRENEURS - Rajam, Sirumalar; Soundararaja, K. V. (International Journal of Research -GRANTHAALAYAH, 2016)
Women constitute around half of the total world population. So is in India also. They are, therefore, regarded as the better half of the society. In traditional societies, they were confined to the four walls of houses performing household activities. In modern societies they have come out of the four walls to participate in all sorts of activities. The global evidence buttress that women have been performing exceedingly well in different spheres of activities like academics, politics, administration, social work and so on. Now, have started plunging into industry also and running their enterprises successfully. Therefore, white discussing on entrepreneurial development, if seems in the fitness on the context to study about the development of women entrepreneurs in the country.